Draw Label Caption (Dlc) Strategy to Improve Students’ Writing Descriptive Text - Wisnu Oktavianda (Channing : Journal of English Language Education and Literature, 2020)
The purpose of this research was to determine whether there was a significant difference between students who were taught using the Draw Label Caption (DLC) Strategy and students who were not taught using the Draw Label Caption (DLC) Strategy to improve the quality of descriptive text written by eighth-graders of SMP Muhammadiyah 2 Karang Tengah in academic year 2019/2020. The type of research used is quantitative research with experimental methods, with a quasi-experimental design. The population was 78 students, the sample was 50 students by purposive sampling. The research was collected using a written description test and analyzed with the Independent t-test SPSS 16, it was found that the t-obtained was higher than t-t (3.060> 2.021) at the significant level α = 0.05 on the two-sided test. This meant that there is a significant difference between the experimental group and the control group. So the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that the Draw Label Caption (DLC) strategy has a significant on the improvement of the ability to write the descriptive text of eighth-graders of SMP Muhammadiyah 2 Karang Tengah.